Phonological analysis of Arabic diphthongs in defective verbs. - Mohamad Isa, Abdul Azim; Nordin, Fitri Nurul’ain; Zakaria, Muhamad Zaidi; Amat Suparia, Fariz Azzuan; Mohamed Raffi, Muhammad Syaffiq; Hassan, Abd Rauf (Maulana Malik Ibrahim State Islamic University, 2024)
The Arabic diphthongs have two sounds, which are /aɪ/ and /aʊ/, each in its nouns and weak verbs. This study aims to analyse phonological rules related to Arabic diphthongs and syllable segmentation among Arabic diphthongs. Qualitative methods are applied in this research wherein content analysis is conducted using Chomsky and Halle’s phonological rules (1968) and Crowley (1987) theory to analyse all data. The data are collected from the Arabic dictionary called Mu’jam Taşrīf al-`af’āl al-‘arabiyyah and the data are then divided into two categories, namely sound /w/ and /y/. The study observes that the Arabic diphthong sounds are found in in the forms of nouns and defective verbs with suffixes other than /a/, /t/ and /w/. The study finds that in Arabic, diphthong sounds are deleted in defective verbs when the suffix consists of two phonemes, and these sounds transform into long vowel sounds upon the addition of /a/, indicating the third-person singular male in the past tense. The suffixes /t/ and /w/ similarly convert the diphthong to a basic vowel. This study concludes that phonological changes occur more frequently in Arabic defective verbs than in nouns, following certain rules. Additionally, syllable segments change as well when the glide sounds forming diphthongs are deleted.